ANALYSIS OF MARKET DISCIPLINE MECHANISM IN INDONESIA BANKING INDUSTRIES - Moch. Doddy Ariefianto; Yuswanto Yuswanto (Journal of Economics, Business, and Accountancy Ventura, 2013)
The market discipline is considered an important element for creating a sound and efficient operation ofthe banking industry. It can be shown by the response of investors and depositors of the business operationsand management in relation to the risk of a bank. Theoretically, there are hypotheses must be accomplishedin order to effectively market discipline occurs. The first hypothesis, whether the marketdiscipline provides a signal for of banks regarding the existence of a certain conditions which is inconsistentwith sound and efficient bank and business operation (Disciplining Signal Hypotheses; DSH).The second, bank management will respond to the signal by making efforts towards the implementationfor correction on the business in line with expectations (Corrective Response Hypotheses; CRH). Theverification used the empirical accounting data and market commercial banks with a total of 110 frequencyof semester 2000-2010 (panel data, 1843 observations). Empirical analysis model used regressionpanel data. The estimation results indicate that DSH gained strong empirical support. On the otherhand, the result of estimation involved in CRH is still significantly weak. This indicates that the marketdiscipline mechanism has not operated optimally in Indonesian banking industries. Therefore, correctionis required especially on regulatory mechanisms to improve the quality of banking.